Greenhouse Gas Estimation from Rice Fields in Simbalai Village, Loea Subdistrict, East Kolaka Regency - La Ode Midi; La Ode Siwi; La Ode Muhammad Erif; Nindi Darmayanti (Indonesian Journal of Geography, 2026)
This study aims to determine the amount of greenhouse gas emissions in the rice paddy agricultural sector in Simbalai Village, Loea District. The research was conducted in April 2022 in Simbalai Village, Loea District, which has 167 hectares of wet-rice fields. The methods used in this research included observation of paddy rice areas, data collected from the Agricultural Extension Center (BPP) of Loea District, and interviews. The sampling in this study employed a purposive sampling method, with key informants comprising rice farmers selected based on their knowledge and involvement in rice cultivation practices. The technique to determine the amount of greenhouse gas emissions involved using data on agricultural activities in the village, obtained from records maintained by the Loea District Agricultural Extension Center (BPP), and then analyzing the data based on PERMEN No.73 of 2017, which provides guidelines for implementing and reporting the National Greenhouse Gas Emission Inventory. The results of this study indicate that emissions from irrigated rice farming activities include 640.5 tons of CO2-eq/year of CH4, and from rain-fed rice fields, 178.5 tons of CO2-eq/year of CH4. Additionally, CO2 emissions from using urea fertilizer amounted to 787.3 tons C/year, and N2O emissions from using urea fertilizer amounted to 272.2 tons CO2-eq/year. The total emissions amounted to 1878.58 tons of CO2-eq/year.Received: 2024-10-21 Revised: 2025-08-25 Accepted: 2026-04-22 Published: 2026-04-28